Cryptogein and capsicein promote defence responses in Quercus suber against Phytophthora cinnamomi infection (European Journal of Plant Pathology, 2012)
The decline of cork oak (Quercus suber) stands in Iberian Peninsula is associated with infection by Phytophthora cinnamomi. Most Phytophthora species secrete elicitins, which can enhance defence reactions against some pathogens. Here cytological and physiological effects of the elicitins cryptogein and capsicein on cork oak root infection by P. cinnamomi were evaluated. The progression of the pathogen in root tissue and its effects on total fatty acid (TFA) composition of roots and leaves were analysed in seedlings. Net photosynthesis (Pn), stomatal conductance (gs ), chlorophyll a fluorescence measurements (quantum yield of linear electron transport ϕe , photochemical quenching qP, non-photochemical quenching NPQ) and carotenoid determinations were carried out in well established (4 months) plants. In elicitin-treated roots, 2 days after inoculation, the pathogen which presented loss of viability and membrane degradation was mainly restricted to the intercellular spaces of the cortical parenchyma, and did not reach the vascular cylinder. Electron dense materials accumulated in the intercellular spaces of the cortex next to disorganized hyphae, suggested to be related with defence reactions. Cryptogein (or its interaction with P. cinnamomi) induced enhanced lipid synthesis in leaves, which may contribute to preserve membrane stability. P. cinnamomi decreased Pn , gs , ϕe , and qP, whereas elicitintreated plants displayed values similar to controls. Overall, the results indicated a resistance response of cork oak against this oomycete, induced by the elicitins.